PENANAMAN NILAI-NILAI ISLAM MODERAT PADA ANAK USIA DINI DALAM KELUARGA SEBAGAI UPAYA MENANGKAL RADIKALISME - Rosyida Nurul Anwar (Al Fitrah: Journal Of Early Childhood Islamic Education, 2021)
The radicalism movement became increasingly visible when various terror incidents appeared in various parts of the world, including in Indonesia. The emergence of extremism has slightly disturbed diversity in Indonesia. The involvement of children in the family has recently become a series of acts of terrorism, in other words, terrorist acts take advantage of early childhood. The family has a central role in efforts to ward off radicalism in early childhood. Cultivating moderate values in early childhood requires cooperation between husband and wife in tarbiyatul awlad. The purpose of this study is to describe moderate Islamic values that need to be instilled in early childhood as an effort to curb radicalism. The method used is descriptive qualitative by observing the situation and national conditions. The results showed that the attitude of commitment to nationality, nationality, tolerance, humanity, and local wisdom are values that need to be instilled in early childhood in the family as an effort to prevent radicalism. It is hoped that a moderate attitude in religion from an early age will provide a new oasis in religious life today and in the future.